1996
DOI: 10.1038/ng0596-117
|View full text |Cite
|
Sign up to set email alerts
|

A single BRCA2 mutation in male and female breast cancer families from Iceland with varied cancer phenotypes

Abstract: The BRCA2 gene on chromosome 13 has been shown to be associated with familial male and female breast cancer. Here we describe a study on BRCA2 in 21 Icelandic families, including 9 with male breast cancer. We have previously reported linkage to the BRCA2 region in an Icelandic male breast cancer family and subsequently found a strong indication of linkage to BRCA2 and the same BRCA2 haplotype in breast cancer cases from 15 additional families, indicating a common origin. We describe a five base-pair deletion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
284
1
4

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(299 citation statements)
references
References 8 publications
10
284
1
4
Order By: Relevance
“…The highly significant excess of male breast cancers (based on two cases) raises the possibility of a genetic basis, as male breast cancer has been found associated with the BRCA2 gene (Thorlacius et al, 1996;Friedman et al, 1997). The cases, however, were not from families in which breast cancer or ovarian cancer are known to have occurred in women; they were not known to have any ancestors in common, and had not been tested for BRCA2.…”
Section: Cancer Incidence In the Falklandmentioning
confidence: 99%
“…The highly significant excess of male breast cancers (based on two cases) raises the possibility of a genetic basis, as male breast cancer has been found associated with the BRCA2 gene (Thorlacius et al, 1996;Friedman et al, 1997). The cases, however, were not from families in which breast cancer or ovarian cancer are known to have occurred in women; they were not known to have any ancestors in common, and had not been tested for BRCA2.…”
Section: Cancer Incidence In the Falklandmentioning
confidence: 99%
“…1 Unlike BRCA1 mutations, germline mutations of BRCA2 are involved in the development of a considerable number of male breast cancer. [2][3][4][5] LOH on chromosome 13q12-13 was reported in 20-60% of sporadic breast tumors. 6 -8 Such high frequency of allelic loss at BRCA2 locus points to an important role of this gene in the development and progression of sporadic breast cancer.…”
mentioning
confidence: 99%
“…12 BRCA2 mutations were detected in individuals with different tumor types, including male and female breast cancer and cancer of the prostate, pancreas, ovary, colon, stomach, thyroid, cervix and endometrium. 3,13 Tumors from BRCA2 mutation carriers usually show loss of heterozygosity on chromosome 13q12-13 and the losses always involve the wild-type chromosome. 13,14 Similarly, in our study all tumors of BRCA2 carriers showed LOH at BRCA2 locus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, BRCA2 was found to be more associated with male breast cancer compared to BRCA1 (Wooster et al, 1994). Patients with BRCA2 mutations were also found to be at a higher risk with a variety of other cancers including carcinomas of pancreas, prostate and colon (Thorlacius et al, 1996;Phelan et al, 1996;Gudmundsson et al, 1995;Tonin et al, 1995). The BRCA2 gene is composed of 27 exons and encodes a protein of 3418 amino-acids with no signi®cant homology to any known protein Bork et al, 1996).…”
mentioning
confidence: 99%